Analyzing 5th Grade Science Textbook Activities in Light of the Turkish Century Education Model: A STEM and Design Thinking Perspective - Doğanay, Kamil; Pektaş, Murat (Social Scientific Centered Issues, 2025)
This study examined how the activities in the 5th grade Science textbook, updated within the Turkish Century Education Model (TCEM), were structured in terms of STEM education and the Design Thinking (DOT) approach. Using document analysis, the 2024 Science textbook published by the Ministry of National Education was analyzed. Fifty activities were evaluated based on the four STEM components (science, technology, engineering, mathematics) and five DOT stages (empathy, define, ideate, prototype, test). Findings showed that the activities were mostly science-focused, while technology, engineering, and mathematics were less represented. About half of the activities involved some DOT stages, yet creative production phases such as ideation, prototyping, and testing were limited. Only 40% of the activities included both STEM and DOT components. The qualitative analysis indicated that most activities emphasized observation and information gathering rather than creative thinking or problem-solving. This suggests that the TCEM’s vision of raising productive and versatile individuals is only partially reflected in the textbook. It is recommended that textbook activities be redesigned to more fully integrate STEM and DOT approaches, providing students with interdisciplinary, student-centered, and production-oriented learning experiences that support 21st-century skills.
Keywords: STEM Education; STEM Eğitimi; STEM Education; Design Thinking; Turkish Century Education Model; Science Course; Qualitative Content Analysis